Emergy-based environmental accounting of graphite anode material production. (10th March 2022) - Rui, Xue; Geng, Yong; Zhuang, Mufan; Xiao, Shijiang; Sun, Xin
Abstract: Natural graphite is often regarded as a critical mineral because it is currently the most widely used battery anode material (BAM) for commercial lithium-ion batteries. However, studies on evaluating the criticality of natural graphite are still lacking, especially how to evaluate its substitutability from an environmental perspective. Emergy is defined as the sum of all the solar energy required to generate a product or service and emergy synthesis is one effective method for environmental accounting. This study employs an emergy synthesis method to compare the efficiency and sustainability of BAM production processes with different raw material inputs - natural graphite and its major substitute synthetic graphite. The overall environmental performance of graphite BAM production is also examined by evaluating the contribution of natural capital and ecosystem services. Results show that the total emergy input for natural graphite BAM production was 4.72E+10 sej/g, dominated by natural graphite deposit, while the total emergy input for synthetic graphite BAM production was 2.34E+10 sej/g, dominated by petroleum coke and electricity. Based on the emergy indicators, the BAM production from synthetic graphite is considered as a preferable option because such production process will lead to better economic and environmental performances and improve the overall resource efficiency. These results also imply that the criticality of natural graphite might be overestimated since the substitution of synthetic graphite in BAM manufacturing is economically and environmentally feasible. Graphical abstract: Image 1 Highlights: Graphite is one key critical mineral for battery anode material. Emergy synthesis is applied to evaluate the overall sustainability of graphite battery anode manufacturing. Anode made by synthetic graphite is a more sustainable option. The criticality of natural graphite is overestimated since synthetic graphite can substitute natural graphite.